Hubungan Praktik Penggunaan Fasilitas Sanitasi dan Praktik Personal Hygiene dengan Kejadian Diare Pada Balita di Kelurahan Bandarharjo Kota Semarang - Budiyono, Budiyono; Wuryanto, M. Ari (Jurnal Promosi Kesehatan Indonesia, 2007)
Background : The incidence of diarrhea is 22.117 in Semarang City in 2004 9.583 cases among then accured on children under five years. In the North Semarang, the incidence of diarrhea on children under five years is 617 cases. The factors influences of diarrhea occurrence are knowledge of mother the availability of sanitary facilities and personal hygiene practices.This research aim to identity the relationship between sanitation facilities and personal hygiene practices and the incidence of diarrhea on children under five years in Bandarharjo, Semarang CityMethod : This research is observational analytic method using cross sectional design. The number of sample are 39 mothers who have children under five years. Statistical analysis used Chi-Square test with Ã¡=5%.Result : Result of this research showed tha the incidence of diarrhea is 13 cases (33,3%) on children under five years. Respondents washed hands before eating and drinking is 34 (87,2%), respondents have never whashed hands after defecation is 25 (64,1%), respondents using of pit/latrine is 35 (89,7%), respondents using of source of proper drinking water is 28 (71,8%). This research was cocluded that it was o significant association between washing hands after defecation, using pti/latrine for defecation and diarrhea occurance on children under five years. It was a significant association between source of proper drinking water and diarrhea occurance on children under five years in Bandarharjo, Semarang.Keywords : Sanitation, hygiene, practice, diarrhea, children under five years